Molecular and Parasitological Survey of Ovine Piroplasmosis, Including the First Report of Theileria annulata (Apicomplexa: Theileridae) in Sheep and Goats from Turkey - Ozubek, S.; Aktas, M. (Oxford Univ Press Inc, 2017)
Blood and tick samples were collected from 333 apparently healthy sheep and 257 goats as well as 10 sheep exhibiting clinical signs of babesiosis in Adana, Gaziantep, and Adiyaman Provinces in southern Turkey. Fully engorged female ticks were selected and maintained in an incubator until they oviposited. The tick carcasses and their egg masses were examined. Piroplasms compatible with Babesia spp. and Theileria spp. were observed in both symptomatic and asymptomatic small ruminants. Genomic DNA isolates from blood of ovine, tick samples, and egg masses were screened for piroplasms by utilizing 18S rRNA polymerase chain reaction and reverse line blotting (RLB) assays. Parasitemia ranged from 0.01% to 5.6% of erythrocytes in clinical cases. RLB showed positivity in 239 (40.5%) of the sampled apparently healthy sheep and goats and revealed the presence of three Theileria and one Babesia species. Theileria ovis was the most prevalent (35.4%), followed by Babesia ovis (5.4%), Theileria annulata (3.9%), and Theileria sp. MK (0.3%). Thirty-two small ruminants infected with T. ovis were also infected with B. ovis. One animal infected with T. ovis was also infected with Theileria sp. MK. Ticks were identified as Rhipicephalus bursa, Rhipicephalus turanicus, Hyalomma excavatum, Haemaphysalis parva, and Hyalomma anatolicum. Egg masses of two female R. bursa carcasses were infected with B. ovis. This is the first report of theileriosis caused by T. annulata in sheep and goats in Turkey.
Keywords: Theileria; Babesia; PCR; reverse line blot; sheep